Analisis Pembelian Konsumen Kafe Santai Gondanglegi Dilihat dari Harga, Kualitas Produk dan Kualitas Pelayanan - Sinollah, Sinollah; Tiffuri, Muhammad (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
This study aims to determine the effect of price, product quality, and service quality on purchasing decisions at Santai Gondanglegi Café. The variables in this study are price, product quality, service quality, and purchasing decisions. The research method used in this study uses quantitative methods. In collecting data used questionnaires with a likert scale. The population used in this study are consumers who buy at least 2 times with a total of 100 respondents. The results of this study indicate that price has a significant effect on purchasing decisions. Product quality has a significant effect on purchasing decisions. Service quality has a significant effect on purchasing decisions. The influence of independent variables (price, product quality, and service quality) on purchasing decisions is 69.5%. Suggestions to Santai Gondanglegi Café business owners to add food and beverage variants so that consumers are interested in buying. Apart from that, pay attention to facilities such as bathrooms, prayer rooms, and a large vehicle parking area. So that it makes consumers feel comfortable when they come or buy at the Santai Gondanglegi Café.